2021
DOI: 10.1038/s41598-021-97753-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles cargo from head and neck cancer cell lines disrupt dendritic cells function and match plasma microRNAs

Abstract: Extracellular vesicles (EVs) are mediators of the immune system response. Encapsulated in EVs, microRNAs can be transferred between cancer and immune cells. To define the potential effects of EVs originated from squamous cell carcinoma cells on immune system response, we performed microRNA profiling of EVs released from two distinct cell lines and treated dendritic cells derived from circulating monocytes (mono-DCs) with these EVs. We confirmed the internalization of EVs by mono-DCs and the down-regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…In contrast to our study, oral squamous cell carcinoma tissue also showed an enrichment for miR-24-3p compared to peritumoral tissue ( 56 ). Furthermore, the enrichment of miR-24-3p could be found in EVs derived from nasopharyngeal carcinoma cell lines and patient sera ( 57 ), head and neck cancer cell lines ( 58 ) and classical Hodgkin’s lymphoma ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, oral squamous cell carcinoma tissue also showed an enrichment for miR-24-3p compared to peritumoral tissue ( 56 ). Furthermore, the enrichment of miR-24-3p could be found in EVs derived from nasopharyngeal carcinoma cell lines and patient sera ( 57 ), head and neck cancer cell lines ( 58 ) and classical Hodgkin’s lymphoma ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…DC-EV function depends on their molecular composition, in particular the concentration of co-stimulatory molecules (CD86, CD80, CD40) and antigen-presenting molecules (MHC-II, MHC-I) [ 286 , 287 ]. It was previously described that TEV cargo (HSP, TLR, HLA g [ 29 ]; S100A8, S100A9, Annexin A1 [ 30 ]; PGE2 [ 288 ]; TGFβ1 [ 289 ]; or microRNAs [ 290 ]), suppress DC maturation, resulting in the loss of tumour cell recognition [ 29 , 30 ]. Moreover, once activated by TEV, DC release their own TEV conveying tumour-associated antigens [ 291 ], which translate in T-cell cross-activation, antigen presentation, and immune tolerance [ 292 , 293 ].…”
Section: Tev Released By Tme Cellsmentioning
confidence: 99%
“…Increasing evidence has highlighted how exosomes represent a mechanism underpinning cancer cell-triggered immune escape by inducing phenotypic changes in different immune cell populations. Paula Silva et al evaluated the potential effects of EVs originating from HNSCC cells on immune system response [ 47 ]. In this study, monocyte-derived dendritic cells (mono-DCs) were treated with EVs derived from oropharyngeal squamous cell carcinoma (OPHSCC) and OSCC cell lines [ 47 ].…”
Section: The Function Of Exosomes In Hnsccmentioning
confidence: 99%
“…Paula Silva et al evaluated the potential effects of EVs originating from HNSCC cells on immune system response [ 47 ]. In this study, monocyte-derived dendritic cells (mono-DCs) were treated with EVs derived from oropharyngeal squamous cell carcinoma (OPHSCC) and OSCC cell lines [ 47 ]. Impairment of mono-DC maturation and migration was observed following EV internalization.…”
Section: The Function Of Exosomes In Hnsccmentioning
confidence: 99%
See 1 more Smart Citation